Efforts to Improve Learning Outcomes of Class X Science1 Students for the 2020/2021 Academic Year on Bacteria Material Using Cooperative Learning Method - Mulyani, Refliyati; Kintu Nihan, Aditya Rahman (Lembaga Penelitian dan Pendidikan Mandala, 2024)
The research aims to improve biological learning outcomes on bacterial material through cooperative learning with the jigsaw method for students of the X grade of IPA1 MAN 1 Serang in the Odd Semester of the 2020/2021 academic year. The study was conducted for six months, from July to December. The subject of the study was 32 students of the X grade of the 1st semester of Odd MAN 1 Serang. The class action research was conducted in two cycles. Each cycle consists of four stages: planning, taking action, observing, and reflecting. Data analysis used comparative descriptive analysis by comparing the initial values of class action research from the initial and final conditions. Data collection techniques using observation, documentation, testing, and non-testing techniques. Data is collected from no treatment conditions, cycles I and II results. The study's results show an increase of 8% in the average of the initial condition to cycle 1 with an average of 75 to 81. Cycle I to Cycle II increased by 13.58%, from 81 to 92. Initial to final conditions increase by 22.66% from the average value of 75 to 90. Students' learning activity and motivation increased.